Development and gamma-scintigraphy study of Hibiscus rosasinensis polysaccharide-based microspheres for nasal drug delivery. (1st November 2016) - Sharma, Nitin; Tyagi, Shanu; Gupta, Satish Kumar; Kulkarni, Giriraj Thirupathirao; Bhatnagar, Aseem; Kumar, Neeraj
Abstract: Objective: This work describes the application of natural plant polysaccharide as pharmaceutical mucoadhesive excipients in delivery systems to reduce the clearance rate through nasal cavity. Methods: Novel natural polysaccharide ( Hibiscus rosasinensis )-based mucoadhesive microspheres were prepared by using emulsion crosslinking method for the delivery of rizatriptan benzoate (RB) through nasal route. Mucoadhesive microspheres were characterized for different parameters and nasal clearance of technetium-99m ( 99m Tc)-radiolabeled microspheres was determined by using gamma-scintigraphy. Results: Their Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) studies showed that the drug was stable during preparation of microspheres. Aerodynamic diameter of microspheres was in the range 13.23 ± 1.83–33.57 ± 3.69 µm. Change in drug and polysaccharide ratio influenced the mucoadhesion, encapsulation efficiency and in-vitro release property. Scintigraphs taken at regular interval indicate that control solution was cleared rapidly from nasal cavity, whereas microspheres showed slower clearance ( p < 0.005) with half-life of 160 min. Conclusion: Natural polysaccharide-based microspheres achieved extended residence by minimizing effect of mucociliary clearance with opportunity of sustained delivery for longer duration.